2019
DOI: 10.1111/jcmm.14863
|View full text |Cite|
|
Sign up to set email alerts
|

CircNr1h4 regulates the pathological process of renal injury in salt‐sensitive hypertensive mice by targeting miR‐155‐5p

Abstract: Circular RNAs are a class of widespread and diverse endogenous RNAs that may regulate gene expression in various diseases, but their regulation and function in hypertensive renal injury remain unclear. In this study, we generated ribosomal-depleted RNA sequencing data from normal mouse kidneys and from injured mouse kidneys induced by deoxycorticosterone acetate-salt hypertension and identified at least 4900 circRNA candidates. A total of 124 of these circRNAs were differentially expressed between the normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…The reaction between miR-155-5p and circNr1h4 is basically competitive, where the silencing of circNr1h4 or overexpression of miR-155-5p considerably decreased Far1 levels and increased ROS production. Therefore, miR-155-5p may be involved in the pathology of hypertensive kidney injury [ 73 ]. The involvement of miR-155-5p in the pathophysiological pathway to the development of diabetic kidney disease is probably explained by the signaling axis of p53 and sirt1 genes with regulation of autophagic and fibrotic processes in renal tubular injury.…”
Section: Micrornas Associated With Aki Induced By Sepsis or Nephromentioning
confidence: 99%
“…The reaction between miR-155-5p and circNr1h4 is basically competitive, where the silencing of circNr1h4 or overexpression of miR-155-5p considerably decreased Far1 levels and increased ROS production. Therefore, miR-155-5p may be involved in the pathology of hypertensive kidney injury [ 73 ]. The involvement of miR-155-5p in the pathophysiological pathway to the development of diabetic kidney disease is probably explained by the signaling axis of p53 and sirt1 genes with regulation of autophagic and fibrotic processes in renal tubular injury.…”
Section: Micrornas Associated With Aki Induced By Sepsis or Nephromentioning
confidence: 99%
“…Although circular RNAs are attracting a good deal of attention, there has been little research in the field of circRNAs correlated with SSBP until now. Lu et al (2020) found that CircNr1h4 is involved in the pathological process of salt-sensitive hypertension with renal injury by sponging miR-155-5p as a ceRNA. Additionally, Cheng and Joe (2017) compared the circRNA expression of the Dahl salt-sensitive rat, the Dahl salt-resistant rat, the spontaneously hypertensive rat, and the Wistar Kyoto rat by microarray analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have proved that circular RNAs can compete with mRNAs for target binding sites of miRNAs to in turn regulate the expression of mRNAs [15,23]. Furthermore, in recent years, the protein-binding function and the potentiality translating into short-peptide has attracted increasing attention [24,25], which may…”
Section: Discussionmentioning
confidence: 99%